Wooden school furniture for underdeveloped and developing countries - Eckelman, C. (Malaysian XXI IUFRO World Congress Organising Committee, 2013)
In many underdeveloped and developing regions of the world, school furniture is poorly designed, of low quality, and often unfit for school use, yet it is costly and consumes a disproportionate share of limited educational budgets. This situation need not continue. Our research indicates that attractive, well-designed, durable, maintenance-free furniture can be produced from locally available woody materials including plantation thinnings and semi-processed materials such as pallet deck boards by local industry. Only the simplest machining and joinery processes are required to construct the furniture. Cost of the furniture is generally less than that of competing products, yet performance tests indicate that the furniture produced is several times more durable than furniture currently in use. Production techniques vary from those best-suited to cottage industries to those more appropriate for small factories in more developed areas. Small stems can be converted into squares or dowels that are subsequentlty cut into furniture parts, or the stems can be converted into small strips that are subsequently used to fabricate individual furniture parts or entire frames. Curved laminated construction can be used when woods can be easily steam bent. Creep bending with simple jigs can also be used to form parts with sharp corners and straight sides. Green bending can be used to form parts with mild bends suah as seat and back slats. Simple chemical bending with household ammonia may also be used to form extreme bends in the ends of such items as seat slats. Cross lap laminated construction can be used with those woods in which only short lenghts of clear wood can be obtained or which have poor bending characteristics. This method of construction produces strong, durable, geometrically accurate frames with very simple equipment. Round mortise and tenon construction provides a simple yet strong and reliable method of connecting members and side frames together. Round tenons may be produced on a conventional wood lathe or they may be cut with a simple hole saw. In conclusion, preliminary results indicate that sturdy, well-designed school furniture can be produced from small woody stems and other wood residues by a variety of production processes - some best suited to cottage industries, others to more developed industries. Thus, school furniture and the accompanying production processes can be matched to the level of development of essentially any interested country. Finally, none of the processes involved in the construction of the frames are inherently costly so that attractive, sturdy, easily maintained furniture can be produced at modest cost in any developing country.